A matemática recreativa e suas potencialidades didático-pedagógicas à luz da teoria da objetivação - Bezerra, Maria da Conceição Alves (2021)
This research is a study on Recreational Mathematics, and it approaches its conceptual and didactic-pedagogical aspects as well as its most frequent tasks: mathematical games, mathematical puzzles and Recreational Problems. The guiding question of the research is: which characteristics of Recreational Mathematics can be evidenced through the principles of the Theory of Objectivation, enhancing its use in the classroom? As a research objective, we proposed to investigate the theoretical-methodological contributions of the Theory of Objectification to the proposition of Recreational Mathematics tasks in the classroom. In this context, the established thesis is that Recreational Mathematics tasks, based on the Joint Labor and the Community Ethics of the Theory of Objectification, contribute to the student's mathematical formation as a citizen in a historical-cultural community. To this end, a mapping activity was carried out focusing on research in Recreational Mathematics using Theses and Dissertations produced between 1994 and 2018. This mapping contributed to the understanding of Recreational Mathematics as a methodological approach that can provide motivation, pleasure and fun, among other positive aspects. This study has a qualitative exploratory approach, uses the multimodal analysis method and is based on the Theory of Objectification. Thus, a Didactic-Pedagogical proposal was organized in the light of the Theory of Objectification, in order to present to the Mathematics graduate students the Recreational Mathematics in its most relevant aspects, both from the point of view of problem solving and pedagogical reflections. Thus, an exploratory workshop on Recreational Mathematics was developed for teachers and students of Mathematics Degree. As for the pedagogical intervention, it consisted of five tasks to be developed with the the graduates of Mathematics degree at the Federal University of Rio Grande do Norte (UFRN/Natal). However, only Task 1 of the proposed intervention was applied. As for the workshop analysis, we found that students and teachers were interested in reading and solving the Recreational Problem in a fun and pleasurable way, promoting a work of human cooperation, nourished by the ethics of responsibility, commitment and care for others. In relation to Task 1 provided, the students with ethical and reflective thoughts, as they worked in a collaborative environment through Joint Labor and supported by a Community Ethics. Such results indicate that the insertion of Recreational Mathematics tasks in the training of Mathematics teachers allows greater dynamism and playfulness in classes.